Decreased placental glypican expression is associated with human fetal growth restriction. (15th January 2019) - Gunatillake, T.; Chui, A.; Fitzpatrick, E.; Ignjatovic, V.; Monagle, P.; Whitelock, J.; Zanten, D.; Eijsink, J.; Borg, A.; Stevenson, J.; Brennecke, S.P.; Erwich, J.J.H.M.; et al.
Abstract: Placental mediated fetal growth restriction (FGR) is a leading cause of perinatal morbidity and mortality. Heparan sulphate proteoglycans (HSPG) are highly expressed in placentae and regulate haemostasis. We hypothesise that altered expression of HSPGs, glypicans (GPC) may contribute to the development of FGR and small-for-gestational-age (SGA). GPC expression was determined in first-trimester chorionic villous samples collected from women with later SGA pregnancies and in placentae from third-trimester FGR and gestation-matched uncomplicated pregnancies. The expression of both GPC1 and GPC3 were significantly reduced in first-trimester SGA as well as in the third-trimester FGR placentae compared to controls. This is the first study to report a relationship between altered placental GPC expression and subsequent development of SGA/FGR. Highlights: Heparan sulphate proteoglycans are abundantly expressed in human placentae. Placental glypican expression is reduced in third-trimester FGR samples. Reduced glypican expression in first-trimester pregnancy may contribute to the development of FGR.